Kitchen. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows an empty kitchen attached to the hospital unit at Heart Mountain Relocation Center.